# Deﬁnition. For z ∈ C we deﬁne cos z = 1 iz (e + e−iz ); 2 sin z = 1 iz (e − e−iz ); 2i cosh z = 1 z (e + e−z ); 2 sinh z = 1 z (e − e−z ).

2

Remark In all of what follows we will make use of the fundamental identity (∗) ez+w = ez ew , z, w ∈ C.

Here is a proof of (*) in which we leave out the nontrivial justiﬁcation of some of the steps. We have ez+w = =
n=0 ∞

(z + w)n n! n=0

z m wn−m m! (n − m)! m=0 z m wn−m m! (n − m)! n=m zm m! zm m! wn−m (n − m)! n=m wn n! n=0
∞ ∞ ∞

n

=
m=0 ∞

=
m=0 ∞

=
m=0 ∞

=

zm w e m! m=0

= ez ew . From the deﬁnitions we immediately deduce that (1) and that (2) cos2 z + sin2 z = 1, cosh2 z − sinh2 z = 1. eiz = cos z + i sin z

From (*) we obtain the addition formulae (3) sin(z + w) = sin z cos w + cos z sin w, cos(z + w) = cos z cos w − sin z sin w.

Diﬀerentiating term by term the power series that deﬁne the exponential function we ﬁnd that (4) d z e = ez . dz

d One could also use (*) to deduce (4). For any constant a we have dz f (az) = af (az) provided f is diﬀerentiable in the complex; this fact, (1) and the deﬁnitions immediately imply that

(5)

d cos z = − sin z; dz

d sin z = cos z; dz

d cosh z = sinh z; dz 1

d sinh z = cosh z. dz

(2m!) m=0 ∞ ∞ ∞ sin z = ez = zn z 2m z 2m+1 = + . (2m)! m=0 (2m + 1)! m=0 z 2m+1 . y are real we have cos z = 1 i(x+iy) e + e−i(x+iy) 2 1 −y+ix = e + ey−ix 2 1 −y e (cos x + i sin x) + ey (cos x − i sin x) = 2 1 = cos x(ey + e−y ) − i sin x(ey − e−y ) 2 = cos x cosh y − i sin x sinh y. (15) cosh z = cos iz = cos(−y + ix) = cos(−y) cosh x + sin(−y) cosh x = cosh x cos y − cosh x sin y and (16) sinh z = −i sin(iz) = −i sin(−y + ix) = −i(sin(−y) cosh x + i cos(−y) sinh x) = sinh x cos y + i cosh x sin y. (2m)! (2m + 1)! m=0 m=0 (−1)m z 2m+1 . (2m + 1)! m=0 ∞ ∞ ∞ ∞ ∞ ∞ ∞ ∞ ∞ e−iz = cos z = (−1)m z 2m . (13) Changing a sign and dividing by i in the third line of the preceding calculation one obtains sin z = (14) 1 −y e (cos x + i sin x) − ey (cos x − i sin x) 2i 1 = i sin x(ey + e−y ) − sin x(ey − e−y ) 2i = sin x cosh y + i cos x sinh y. Whew! 2 . n! (2m)! (2m + 1)! m=0 (2m)! (2m + 1)! n=0 m=0 m=0 m=0 (−1)m z 2m (−1)m z 2m+1 −i . Finally. n! (2m)! m=0 (2m + 1)! n=0 m=0 z 2m z 2m+1 − .We have (6) This gives (7) Combining (6) and (7) we get (8) We have (10) This gives (11) Combining (10) and (11) we get (12) cosh z = z 2m . (2m + 1)! m=0 ∞ ∞ ∞ e−z = sinh z = If z = x + iy where x. (2m)! m=0 ∞ eiz = (iz)n (iz)2m (iz)2m+1 (−1)m z 2m (−1)m z 2m+1 = + = +i .

Sign up to vote on this title